2010
DOI: 10.4103/0970-0218.69253
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and trend of dengue cases admitted in a tertiary care hospital, Udupi district, Karnataka

Abstract: Background:India is one of the seven identified countries in the South-East Asia region regularly reporting dengue fever (DF)/dengue hemorrhagic fever (DHF) outbreaks and may soon transform into a major niche for dengue infection in the future with more and more new areas being struck by dengue epidemicsObjective:To study the clinical manifestations, trend and outcome of all confirmed dengue cases admitted in a tertiary care hospital.Study Design:Record-based study conducted in a coastal district of Karnataka.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
105
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(141 citation statements)
references
References 9 publications
30
105
6
Order By: Relevance
“…Our findings were contrary to those of some Indian studies which had reported the vulnerability of children to dengue infection [6,17,21]. However, a few hospital based studies have similarly reported increasing infection rates among adults [22][23][24].…”
Section: Resultscontrasting
confidence: 57%
“…Our findings were contrary to those of some Indian studies which had reported the vulnerability of children to dengue infection [6,17,21]. However, a few hospital based studies have similarly reported increasing infection rates among adults [22][23][24].…”
Section: Resultscontrasting
confidence: 57%
“…This explains the availability of health care facilities and utilization of these facilities by the local population is good. A higher occurrence of dengue infection was noted among males in our study which is similar to studies conducted earlier (Garg et al, 2011;Kumar et al, 2010). However, this was discordant with the other study where a female predominance was noticed (Gunasekaran et al, 2011).…”
Section: Resultscontrasting
confidence: 36%
“…Patients in the group with rash and conjuctival injection were the ones with features of DHF. Kumar et al (8) in their study documented that headache was present in 47.6% and rash in 21.7% of patients. Other than the above-mentioned symptoms, gastrointestinal symptoms were more prevalent, of which abdominal pain was present in 42.5% and nausea/vomiting in 28.7% of the study population.…”
Section: Discussionmentioning
confidence: 99%